FAKTOR-FAKTOR YANG MEMPENGARUHI KELEMAHAN PENGENDALIAN INTERNAL PEMERINTAH DAERAH KABUPATEN/KOTA - Rachmawati, Dian Eka; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of economy growth, local government size, local own source revenue (PAD), local complexity, and capital expenditure to the weaknesses of internal control in local government. The samples are 38 local governments of districts/cities in East Java province in 2011-2013 periods. The secondary data of this research is the Summary of the Result Semester Examination (IHPS), data of PDRB, data of district amount, and data of the Report of Examination Result of Local Government Financial Report (LKPD) from the Audit Board of the Republic of Indonesia (BPK) East Java Province representative. The examination has been done by using SPSS software 20.0 versions i.e. the examination of outlier data, classic assumption test and multiple regressions analysis. The result of classic assumption test show that the data have been normally distributed and the multicolinearity symptoms or even heteroscedasticity symptoms do not occur. The result of t test shows that economy growth variable has positive influence and capital expenditure variable has negative influence to the weaknesses of internal control. Partially the variables i.e. local government size, local own source revenue (PAD), and local complexity havenât significant influence to the weaknesses of internal control of local government.Keywords: weaknesses of internal control, economy growth, size and local government complexity, local own source revenue (PAD), capital expenditure.